ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NILAIPERUSAHAANDENGAN LEVERAGE SEBAGAI VARIABEL MODERATING PADA PERUSAHAAN INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Roxy, Willyam (Asosiasi Dosen Akuntansi Indonesia, 2018)
The aim of this research was to test and to analyze the factors that influence the firm value, represented by its currentratio, return on equity, price earning ratio, investment opportunityset, institutional ownership, manager ownership, inventory turnover, net profit margin,gross profit margin, total asset turnover, operational profit marginand the leverage as moderating variable in chemical and basic industrynsector listed on the Indonesia Stock Exchange either partiallyand simultaneously. The population of this research was 63chemical and basic industry companies registered in Indonesia Stock Exchange from 2011 until 2014. Thesample was selected by using stratified random samplingmethod amounted to 58 companies, so that was gotten 232 observation as the sample research.  The data were processed using the test methods Kaiser – MeyerOlkin (KMO) for thefirst hypothesis and the method of multiple linear regression statistical tests for thesecond  hypothesis, and the residual test for the third  hypothesis by using SPSSsoftware. The research results prove the first hypothesis that the currentratio, institutional ownership, inventory turnover, net profit margin,gross profit margin, total asset turnover andoperational profit marginaffect  the value of the company through the test factors, and the secondhypothesis that the currentratio, institutional ownership, inventory turnover, net profit margin,gross profit margin, total asset turnover andoperational profit marginsimultaneously affect the value of the company and aspartial only currentratio, gross profit margin dantotal asset turnover variables that affect the value of the company. Whenleverage is used as a moderating variable, the leverage is not the variable which moderatingthe correlation between the variable of currentratio, institutional ownership, inventory turnover, net profit margin,gross profit margin, total asset turnover andoperational profit marginwith the firm value in manufacturing companies engaged in the chemical and basic industry sector company registered in the Indonesian stock exchange.